Utilization of Metarhizium as an insect biocontrol agent and a plant bioinoculant with special reference to Brazil - Mesquita, Emily; Hu, Shasha; Lima, Tais B.; Golo, Patricia Silva; Bidochka, Michael J. (Frontiers in Fungal Biology, 2023)
Brazil has a long history in biological control and has the largest program in sugarcane agriculture to which a biocontrol program is applied. This achievement is, at least, partly due to the utilization of the entomopathogenic fungi Metarhizium. This well-known fungal genus exhibits pathogenicity against a broad range of arthropod hosts and has been applied globally as a biocontrol agent. This fungus is also a root symbiont and in this capacity it is a plant growth promoter. However, this feature (i.e., as a plant symbiont) has yet to be fully explored and implemented in Brazil, although the number of reports demonstrating Metarhizium's utility as a plant bioinoculant are increasing. The Brazilian bioproduct industry targets agricultural pests and is limited to two Metarhizium species represented by four fungal isolates as active ingredients. Entomopathogenic fungi have also been successful in controlling arthropods of public health concern, such as the control of mosquitoes which are vectors of diseases. Isolation of new indigenous Metarhizium isolates from a variety of substrates such as soil, insects and plants show a wide genetic diversity within this fungal genus. In this review, we emphasize the significance of Metarhizium spp. for biological control of insects in Brazil. We also suggest that the experience and success of biological control with fungi in Brazil is an important resource for developing integrated pest management and sustainable strategies for pest control worldwide. Moreover, future implementation prospects of Metarhizium as a bioinoculant and possible new advances in the utility of this fungus are discussed.